Legal Protection of Living Law Recognition Reviewed from the Principle of Legality in the Indonesian Criminal Justice System under the Kitab Undang Undang Hukum Pidana (KUHP) Baru Indonesia - Arsoni Andana Sitio (International Journal of Law, Crime and Justice, 2026)
The recognition of living law within the Indonesian Criminal Code reform represents a significant paradigm shift in the national criminal law system. This issue becomes crucial as it raises fundamental questions regarding legal certainty and the principle of legality in criminal law. This study aims to analyze the legal protection of living law recognition reviewed from the principle of legality within the Indonesian criminal justice system. This research employs a normative legal method with statutory, conceptual, and comparative approaches. Legal materials are derived from primary sources such as statutory regulations, particularly the new Criminal Code, as well as secondary sources including legal doctrines and scholarly works. The findings indicate that the incorporation of living law into the Criminal Code introduces a flexible legal framework that accommodates local wisdom; however, it simultaneously creates potential tensions with the principle of legality, particularly concerning predictability and clarity of criminal norms. This study recommends strengthening normative boundaries and interpretative guidelines to ensure that the application of living law remains consistent with fundamental criminal law principles.